PENGARUH SKEPTISISME PROFESIONAL, PELATIHAN PROFESIONAL, DAN TEKANAN ANGGARAN WAKTU TERHADAP KUALITAS AUDIT - Rara Anisah Putri (2022)
This study aims to examine the effect of professional skepticism, professional training, and time budget pressure on quality of audit. The sampel used in this study was an auditpr that work at public accounting firm in DKI Jakarta. Sampling was carried out using a physical and digital questionnire. Total of sample that has been collected was 54 respondents. The data analysis used in this study was SmartPLS program or Partial Least Square with a significant level of 5%. The result of this study indicate that (1) Professional Skepticism has a significant effect on Audit Quality, (2) Professional Training has no effect on Audit Quality, (3) Time Budget Pressure has a significant effect on Audit Quality.